Economic assessment of land: scientific, legislative and regulatory problems of development - Tretiak, A.; Tretiak, V.; Kovalyshyn, O. (Land Management, Cadastre and Land Monitoring, 2022)
The decision to cancel land economic assessment out of the land valuation works needs scientific substantiation and consideration of the world practice of its application.The research aims to study how the concept of “economic assessment” in used in the world practice, as well as analyzes its essence and performed tasks. The article supplies analysis of the legislative and regulatory problems of development of the economic assessment of land, land resources and land use as an important economic instrument of land relations regulation and territorial spatial development of land use in Ukraine. The research examines the thesaurus framework concerning public requests for the notions of “economic assessment of land”, “economic assessment of land use”, “economic assessment of land resources” and “economic assessment of natural resources”, “land valuation”, “land use valuation” and “land resources valuation”. It is confirmed that the concepts of “economic assessment of land”, “economic assessment of land resources”, “economic assessment of natural resources” are less often used in the world practice as compared to such notion as “economic assessment of land use”. However, in the world practice, the most widely used notion is “land use valuation”, the second position is taken by “land resources valuation”, whereas “land valuation” is rarely used. It is confirmed that the notion of “economic assessment” is up-to-date and is widely used in the developed market economies. In Ukraine, the concept of “economic assessment of land” is not quite correct. To activate scientific researches and to shape the legislative and regulatory supply for development of economic assessment of land and other natural resources, as well as land use, the work clears up the conceptual essence, which should be interpreted as a money expression of economic or social value of both economic and environmental assets, determined by natural peculiarities. Findings of the research confirm that economic assessment determines the value of land, land resources and land use that is estimated by the effect, which the land-holder obtains from using the land or other natural resources within the ecosystem area. The research defines their targeted use. It is identified that the objects of economic assessment include land, land resources, land use, ecosystem services, land and environmental losses.Prospects of the further research involves studying the targeted use for effective employment of the economic assessment objects. Key words: economic assessment of land, economic assessment of land use, economic assessment of land resources.